Mitigation of oxidative stress and inflammatory factors, along with the antibrowning and antimicrobial effects of cassia seed microbial fermentation solution - Xie, Haohui; Gu, Quliang; Chen, Weiji; Meng, Xiangyu; Guo, Zhenyu; Zhang, Yue; Li, He (Frontiers in Microbiology, 2024)
Cassia seeds derived from the mature seeds of the leguminous cassia species, exhibit pharmacological effects attributed to their rich composition of various active ingredients, including anthraquinones. Current research predominantly concentrates on pharmaceutical extractions, with limited advancements in fermentation studies. Our study successfully enhanced the content of active compounds such as anthraquinones, flavonoids, and polyphenols through microbial fermentation techniques. Specifically, we optimized a fermentation system through a single-factor experimental design. The antioxidant characteristics of the fermentation solution were confirmed through assays involving HaCaT cells and zebrafish. We observed that the fermentation solution effectively suppressed inflammatory reactions in both RAW264.7 cells in addition to transgenic zebrafish. Additionally, significant inhibition of tyrosinase activity and melanin production was evident within B16-F10 cells and zebrafish. Furthermore, positive outcomes were obtained in antibacterial assays and chick embryo experiments. These findings underscore cassia seed fermentation solution's potential as an eco-safe material in food chemistry and biomedical sciences.